Discovering Structure of Object Representation in the Ventral Visual Pathway from fMRI Data - Lashkari, D; Vul, E; Kanwisher, NG; Golland, P (NeuroImage (Orlando, Fla.), 2009)
The method does not make any assumptions about the spatial extent of the selective regions to avoid constraints on the space of possible selectivity patterns. Since no spatial information is used by the method, we can seamlessly analyze multi-subject data without spatial normalization of the subjects. Conclusions We presented an exploratory method that enables automatic discovery of the patterns of category selectivity in the visual cortex.